Impact of depression on change in coronary heart disease risk status: the Korean Genome and Epidemiology Study (KoGES) - Jang HY; Song YK; Kim JH; Kim MG; Han N; Lee HY; Kim IW; Oh JM (Dove Medical Press, 2018)
Ha Young Jang,1 Yun-Kyoung Song,1 Jae Hyun Kim,1 Myeong Gyu Kim,1 Nayoung Han,1 Hae-Young Lee,2 In-Wha Kim,1 Jung Mi Oh1 1College of Pharmacy and Research Institute of Pharmaceutical Sciences, Seoul National University, Seoul, 2Division of Cardiology, Department of Internal Medicine, Seoul National University Hospital, Seoul National University College of Medicine, Seoul, Republic of Korea Purpose: The objective of this study was to evaluate the association between depression and change in coronary heart disease (CHD) risk status by an analysis of examination data in the general Korean population.Patients and methods: We examined 1,851 men and 1,689 women (aged 43–73 years) for the Korean Genome and Epidemiology Study Ansan between 2005 and 2012. The estimated CHD risk score of participants was calculated using the Framingham CHD risk score in baseline and after 8-year follow-up period. Among them, population with low Framingham CHD risk score (<10%) in baseline (n=1,582) was used for further analyses. The low Framingham CHD risk score participants were assigned to one of two groups based on the Beck depression inventory (BDI) score: no depression (BDI <10) and depression (BDI ≥10). Multivariate logistic regression was performed to test whether depression was associated with participants’ status change to intermediate or high CHD risk score (≥10%) in men and women, respectively, after 8-year follow-up period.Results: Women with depression showed significant higher rates of changing to intermediate or high CHD risk score status when compared with women without depression even after adjusting for age, systolic blood pressure, high-density lipoprotein, and smoking (adjusted odds ratio [OR], 1.54; 95% CI, 1.08–2.03). However, depression was not associated with intermediate or high CHD risk score status in men (adjusted OR, 1.38; 95% CI, 0.95–1.82).Conclusion: This general population-based cohort study provides evidence that depression can affect the risk of changing CHD risk score status in women. Keywords: depressive symptom, beck depression inventory, Framingham coronary heart disease risk score, coronary heart disease risk factor